STUDY OF SERUM LIPID PROFILE AND FASTING BLOOD SUGAR IN POLYCYSTIC OVARIAN SYNDROME - S, SADANANJALI; S, SREEKANTHA; H, AMRUTH (International Journal of Clinical and Biomedical Research, 2016)
Background: Polycystic ovarian syndrome (PCOS) is the multisystemic disorder and most common reproductive endocrinopathy of women during their childbearing years, expressed in wide varieties of clinical signs and symptoms. It is characterized by a varied and often complex array of metabolic and endocrine abnormalities, including hyperinsulinaemia, hyperglycaemia, glucose intolerance and obesity which put women with PCOS at a higher risk for diabetes, hypertension, dyslipidemia, and cardiovascular disease. Objectives: To estimate Fasting blood glucose and lipid profile in women with PCOS and normal females. Materials and Methods: After Ethical Committee Approval, blood samples were collected from 50 diagnosed PCOS cases and 50 healthy controls (premenopausal women); aged 18 to 40 years. Fasting plasma glucose and lipid profile were investigated in both PCOS patients and controls. The correlation between these biochemical parameters were then studied in the PCOS group. Data analysis done using student’s t- test. Results: There was a significant increase in fasting plasma glucose levels in PCOS patients as compared to controls. PCOS women had higher BMI with increased total cholesterol, TGL, LDL-C, VLDL-C and lower HDL-C (P < 0.05) as compared to the controls which was statistically significant. The levels of glucose showed significant positive correlation with total cholesterol (P<0.01), triglycerides(P<0.05), LDL-C (P<0.01) whereas non-significant negative correlation with HDL-C. Conclusion: The findings of this study confirms the association between Glucose, BMI and dyslipidaemia in PCOS and may help to identify women with PCOS at risk of cardio metabolic syndrome thereby confirming the association between PCOS and cardiovascular risk factors.